The CSP (Cardiogenic Shock Prognosis) Score: A Tool for Risk Stratification of Cardiogenic Shock - Tien, Yu-Tzu; Chen, Wen-Jone; Huang, Chien-Hua; Wang, Chen-Hsu; Chen, Wei-Ting; Hung, Chi-Sheng; Lin, Jr-Jiun; Huang, Ching-Chang; Chang, Wei-Tien; Tsai, Min-Shan (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiogenic shock (CS) is a critical condition and the leading cause of mortality after acute myocardial infarction (AMI). Scores that predict mortality have been established but a patient’s clinical course is often nonlinear, thus factors present during acute care management may be explored. This study intended to develop a risk-predictive model for patients with CS. Methods In this observational study, adult patients who received inotropic support at the Emergency Room (ER) from January 2017 to August 2020 and admitted to the cardiac care unit (CCU) with a diagnosis of CS were enrolled in this study. Patients with out-of-hospital cardiac arrest, inotropic support for bradycardia, and survival less than 24 hours after ER arrival were excluded. A total of 311 patients were enrolled and categorized into derivation (n=243) and validation (n=68) cohorts. Results A history of coronary artery disease, multiple inotrope use, ejection fraction less than 40%, lower hemoglobin concentration, longer cardiopulmonary resuscitation duration, albumin infusion, and renal replacement therapy were identified as independent prognostic factors for in-hospital mortality. The cardiogenic shock prognosis (CSP) score was established as a nomogram and three risk groups were identified: low-risk (score ≦115, 0% of mortality), medium-risk (score 116-209, 8.75% of mortality), and high-risk (score ≧210, 66.67% of mortality). The area-under-the-curve (AUC) of the CSP score was 0.941, and the discrimination value in the validation cohort was consistent (AUC=0.813). Conclusions The CSP score represents a risk-predictive model for in-hospital mortality in patients with CS in acute care settings. Patients identified as the high-risk category may have poor prognosis.